2017
DOI: 10.1161/strokeaha.116.015428
|View full text |Cite
|
Sign up to set email alerts
|

Air Pollution Is Associated With Ischemic Stroke via Cardiogenic Embolism

Abstract: Background and Purpose-The aim of the study was to assessed the impact of short-term exposure to air pollution on ischemic stroke subtype, while focusing on stroke caused via cardioembolism. Methods-From a nationwide, multicenter, prospective, stroke registry database, 13 535 patients with acute ischemic stroke hospitalized to 12 participating centers were enrolled in this study. Data on the hourly concentrations of particulate matter <10 μm, nitrogen dioxide (NO 2 ), sulfur dioxide (SO 2 ), ozone (O 3 ), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(38 citation statements)
references
References 35 publications
2
35
0
1
Order By: Relevance
“…The effect of PM 2.5 was stronger in individuals with a history of hypertension or heart disease than in those without (Figure 3). These results are somewhat consistent with a recent study that analyzed data from the single-tiered EMS system in Korea [26], which showed that patients with impaired endothelial function might be more susceptible to ambient air pollution [27,28]. However, although the risks of OHCAs were higher in patients with hypertension or heart disease, the differences between the groups with and without a history of hypertension or heart disease were not significant, with p -values of 0.68 and 0.61, respectively.…”
Section: Discussionsupporting
confidence: 92%
“…The effect of PM 2.5 was stronger in individuals with a history of hypertension or heart disease than in those without (Figure 3). These results are somewhat consistent with a recent study that analyzed data from the single-tiered EMS system in Korea [26], which showed that patients with impaired endothelial function might be more susceptible to ambient air pollution [27,28]. However, although the risks of OHCAs were higher in patients with hypertension or heart disease, the differences between the groups with and without a history of hypertension or heart disease were not significant, with p -values of 0.68 and 0.61, respectively.…”
Section: Discussionsupporting
confidence: 92%
“…[76] Short-term exposure (7 days) to PM 10 and SO 2 is associated with cardioembolic stroke. [77] Qin et al report that obese (BMI ≥ 30 kg/m 2 ) and overweight individuals (BMI 25–29 kg/m 2 ) may experience enhanced effects of air pollution and increased stroke risk. [78]…”
Section: Air Pollution and Strokementioning
confidence: 99%
“…Exposure to ambient air pollution, particularly fine coarse (PM 2.5 ) and thoracic (PM 10 ) particulate matters, nitrogen oxide (NO x ), nitrogen dioxide (NO 2 ), and elemental carbon, has been linked to a wide range of adverse health effects. Epidemiological studies have increasingly shown that air pollution is associated with not only respiratory diseases (Chung et al, ; Li et al, ; Cox, ) but also coronary artery disease (Wolf et al, ; McGuinn et al, ), cardiovascular diseases (Brook et al, ; Franklin et al, ), and cerebrovascular diseases (Stafoggia et al, ) including ischemic stroke (Chung et al, ; Cox, ).…”
Section: Introductionmentioning
confidence: 99%